Tumor growth suppressive effect of IL-4 through p21-mediated activation of STAT6 in IL-4Rα overexpressed melanoma models - Lee, Hye Lim (Oncotarget, 2016)
To evaluate the significance of interleukin 4 (IL-4) in tumor development, we compared B16F10 melanoma growth in IL-4-overespressing transgenic mice (IL-4 mice) and non-transgenic mice. In IL-4 mice, reduced tumor volume and weight were observed when compared with those of non-transgenic mice. Significant activation of DNA binding activity of STAT6, phosphorylation of STAT6 as well as IL-4, IL-4Rα and p21 expression were found in the tumor tissues of IL-4 mice compared to non-transgenic mice. Higher expression of IL-4, STAT6 and p21 in human melanoma tissue compared to normal human skin tissue was also found. Higher expression of apoptotic protein such as cleaved caspase-3, cleaved caspase-8, cleaved caspase-9, Bax, p53 and p21, but lower expression levels of survival protein such as Bcl-2 were found in the tumor of IL-4 mice. In vitro study, we found that overexpression of IL-4 significantly inhibited SK-MEL-28 human melanoma cell and B16F10 murine melanoma cell growth via p21-mediated activation of STAT6 pathway as well as increased expression of apoptotic cell death proteins. Moreover, p21 knockdown with siRNA abolished IL-4 induced activation of STAT6 and expression of p53 and p21 accompanied with reduced IL-4 expression as well as melanoma cell growth inhibition. Therefore, these results showed that IL-4 overexpression suppressed tumor development through p21-mediated activation of STAT6 pathways in melanoma models.